Peran Dukungan Sosial terhadap Kesehatan Mental Korban Bencana Banjir di Kota Sibuhuan - Masjidah Khoiriah Hasibuan (Jurnal Wacana Sosial Nusantara, 2025)
Indonesia is a country prone to natural disasters, one of which is flooding, which often causes material losses and serious psychological impacts on victims. Many flood survivors experience anxiety, deep sadness, and even post-traumatic stress disorder (PTSD), especially when they do not receive adequate social support. This study aims to examine the role of social support on the mental health of flood victims in Sibuhuan City. The methods used were a literature review and analysis of field findings that highlighted the relationship between social support—emotional, instrumental, and informational—and the psychological resilience of survivors. The results of the study showed that victims who received social support were better able to adapt, had lower stress levels, and recovered more quickly from trauma than those who received minimal support. However, the limited number of professionals and the lack of formal psychosocial programs meant that most victims relied solely on assistance from family and volunteers. In conclusion, social support plays an important role in accelerating the mental recovery of flood victims, but its effectiveness would be optimized if it were supported by professional psychological interventions and systematic and sustainable policies.